Pendampingan penyusunan laporan keuangan sederhana untuk UMKM dalam meningkatkan profitabilitas UMKM: Sukoanyar, Kecamatan Wajak, Kabupaten Malang, Provinsi Jawa Timur - Ari Nurcahyo Darmawan; Ayu Rachmawaty; Ninda Rachmawati (JOURNAL INNOVATION AND COMMUNITY SERVICE, 2023)
This research was conducted in the Abepura District of Jayapura in three locations, namely: Sukhoanyar, Wajak, and three micro-enterprise (UMKM) groups consisting of food stalls, general kiosks, and noken creative crafts. The objective of this community service program is to increase the engaged community’s knowledge and skills in entrepreneurship as well as the management of microfinance. This program is done through the identification of UMKM problems, lectures and discussions, entrepreneurship, and microfinance management assistance, and is finished by monitoring and evaluation. Found the results that the UMKM community can utilize the potential of raw materials that have not been utilized maximally through product innovation,but also that they can create simple financial reports for micro-enterprises in order to increase profitability. This program is expected to be completed by continuing to work with the government, the microfinance credit fund body, and other stakeholders to overcome capital and other potential problems at UMKM.